Rapid symptom control in neuroleptic malignant syndrome with electroconvulsive therapy: A case report - Katzell, Lauren; Beydler, Emily; dos Santos, Amílcar Silva; Vijayvargiya, Richa; Carr, Brent R. (Frontiers in Psychiatry, 2023)
Introduction Neuroleptic malignant syndrome (NMS), thought to arise through dopamine antagonism, is life-threatening. While prompt diagnosis of NMS is critical, it may be obscured by other diagnoses, such as malignant catatonia, with overlapping, life-threatening symptoms. Initiation of dopamine-blocking agents such as antipsychotics and abrupt cessation of dopaminergic medications such as amantadine can precipitate NMS. Once NMS is suspected, deft medical management should ensue. Multiple case reports detail electroconvulsive therapy’s (ECT’s) effectiveness in the treatment of NMS. While this relationship is well-documented, there is less literature regarding comparative efficacy of ECT in the acute treatment of NMS-like states precipitated by withdrawal of dopamine agonists, such as amantadine. Case We present a 52-year-old female with schizoaffective disorder bipolar type, with a history of a lorazepam-resistant catatonic episode the prior year that had responded to amantadine. She presented febrile with altered mental status, lead pipe rigidity, mutism, grasp reflex, stereotypy, autonomic instability, and a Bush-Francis Catatonia Rating Scale (BFCRS) of 24, suggesting malignant catatonia versus NMS. There was concern over a potentially abrupt cessation of her amantadine of which she had been prescribed for the past year. Interventions Organic etiologies were ruled out, and a presumptive diagnosis of NMS was made with central dopaminergic depletion from abrupt dopamine agonist (amantadine) withdrawal as the suspected underlying etiology. After intravenous lorazepam and reinduction of amantadine failed to alleviate her symptoms, urgent ECT was initiated. Our patient received an index series of ECT of seven treatments. After ECT #1 she was no longer obtunded, after treatment #2 her symptoms of mutism, rigidity, stereotypy, and agitation showed improvement, and by ECT #3, the NMS had rapidly dissipated as evidenced by stable vital signs, lack of rigidity, and coherent conversation. Conclusion Brisk identification of potentially life-threatening NMS and NMS-like states, including malignant catatonia, warrants a trial of ECT. ECT’s theoretical mechanisms of action coincide with the theoretical pathophysiology of the conditions. It is a viable and safe treatment option for reducing mortality. With prompt initiation of ECT, we obtained rapid control of a condition with a potentially high mortality.